S100A6 is a positive regulator of PPP5C‐FKBP51‐dependent regulation of endothelial calcium signaling. Issue 2 (9th January 2020) - Haldar, Barnita; Hamilton, Caleb L.; Solodushko, Viktoriya; Abney, Kevin A.; Alexeyev, Mikhail; Honkanen, Richard E.; Scammell, Jonathan G.; Cioffi, Donna L.
Abstract: I SOC is a cation current permeating the ISOC channel. In pulmonary endothelial cells, I SOC activation leads to formation of inter‐endothelial cell gaps and barrier disruption. The immunophilin FK506‐binding protein 51 (FKBP51), in conjunction with the serine/threonine protein phosphatase 5C (PPP5C), inhibits I SOC . Free PPP5C assumes an autoinhibitory state, which has low "basal" catalytic activity. Several S100 protein family members bind PPP5C increasing PPP5C catalytic activity in vitro . One of these family members, S100A6, exhibits a calcium‐dependent translocation to the plasma membrane. The goal of this study was to determine whether S100A6 activates PPP5C in pulmonary endothelial cells and contributes to I SOC inhibition by the PPP5C‐FKBP51 axis. We observed that S100A6 activates PPP5C to dephosphorylate tau T231. Following I SOC activation, cytosolic S100A6 translocates to the plasma membrane and interacts with the TRPC4 subunit of the ISOC channel. Global calcium entry and I SOC are decreased by S100A6 in a PPP5C‐dependent manner and by FKBP51 in a S100A6‐dependent manner. Further, calcium entry‐induced endothelial barrier disruption is decreased by S100A6 dependent upon PPP5C, and by FKBP51 dependent upon S100A6. Overall, these data reveal that S100A6 plays a key role in the PPP5C‐FKBP51 axis to inhibit I SOC and protect the endothelial barrier against calcium entry‐induced disruption.